Mobility as the Purpose of Postural Control - Le Mouel, Charlotte; Brette, Romain (Frontiers in Computational Neuroscience, 2017)
Counteracting the destabilizing force of gravity is usually considered to be the main purpose of postural control. However, from the consideration of the mechanical requirements for movement, we argue that posture is adjusted in view of providing impetus for movement. Thus, we show that the posture that is usually adopted in quiet standing in fact allows torque for potential movement. Moreover, when performing a movement - either voluntarily or in response to an external perturbation - we show that the postural adjustments are organized both spatially and temporally so as to provide the required torque for the movement. Thus, when movement is performed skillfully, the force of gravity is not counteracted but actually used to provide impetus to movement. This ability to move one’s weight so as to exploit the torque of gravity seems to be dependent on development and skill learning, and is impaired in aging.